2005
DOI: 10.1074/jbc.m501347200
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Chromo Barrel Domain from the MOF Acetyltransferase

Abstract: We report here the structure of the putative chromo domain from MOF, a member of the MYST family of histone acetyltransferases that acetylates histone H4 at Lys-16 and is part of the dosage compensation complex in Drosophila. We found that the structure of this domain is a ␤-barrel that is distinct from the ␣ ؉ ␤ fold of the canonical chromo domain. Despite the differences, there are similarities that support an evolutionary relationship between the two domains, and we propose the name "chromo barrel." The chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 35 publications
4
60
0
Order By: Relevance
“…Chromodomains have been implicated in binding methylated lysine residues and nucleic acids (reviewed in reference 9), and the chromodomains from the MSL3 and MRG15 proteins could form an aromatic cage implicated in methyl-lysine binding (27,43) and may be required for MSL3 binding to RNA or single-stranded DNA (40). In light of these considerations, the existence of truncated forms of hMSL3L1 that lack an amino-terminal chromodomain was unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…Chromodomains have been implicated in binding methylated lysine residues and nucleic acids (reviewed in reference 9), and the chromodomains from the MSL3 and MRG15 proteins could form an aromatic cage implicated in methyl-lysine binding (27,43) and may be required for MSL3 binding to RNA or single-stranded DNA (40). In light of these considerations, the existence of truncated forms of hMSL3L1 that lack an amino-terminal chromodomain was unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that the SAWADEE domains could be divided into two conserved motifs, each of which may adopt a structure similar to that of the chromo barrel domain (Fig. S6C), a domain family that is similar to the classic chromo domain in sequence but adopts a β-barrel instead of the α + β fold of the chromo domain (27). A subset of the proteins containing chromo barrel or chromo domains has been shown to bind methylated histones and the interaction involves 3-4 conserved aromatic residues that form an "aromatic-cage" to pocket the methylated lysine from histones (28)(29)(30).…”
Section: Loci Where Sirnas But Not Dna Methylation Is Reduced In the mentioning
confidence: 99%
“…These observations are consistent with the far-UV circular dichroism data. In this context, it would be interesting to note that recently a putative nuclear CD from MOF, a member of the histone acetylating transferase from Drosophila, has been shown to have a ␤-barrel structure without the C-terminal helix conventionally found in the structures of CDs (28). Hydrogenbonding interactions between residues located in ␤-strands I and III (Thr 13 -NH, strand I) to Val 34 -CO (strand III) and Val 34 -NH (strand III)…”
Section: Description Of the Three-dimensional Structures Of Cds Of Cpmentioning
confidence: 99%